Growth and yield of Dutch cucumber grown in a protected environment and with alternative organic substrates - Meneses Fernández, Cinthya (2018)
The replacement of imported substrates by local materials is a trend in severaltechnifiedproduction systems, given the cost reduction and the importance of agricultural by-products, formerly considered to be waste. The main objective of this work was to validate the effect of different substrates on the growth and productivity of Dutch cucumber plants under greenhouse conditions. The study took place from October 2012 to January 2013, at the Agricultural Experiment Station Fabio Baudrit, Alajuela, Costa Rica. Variety Fuerte was used and four mixed substrates (volume ratio) made of local raw materials as coconut fiber (FC), oil palm leaf fiber (FP), organic compost (ABO), and sawdust (AS) as well as a commercial treatment (control) constituted by coco coir slabs were analyzed. Substrate water content, plant growth (vegetative phase), and yield were evaluated according to commercial size (S, M, L, XL, and rejected). The growth of Dutch cucumber plants, variety Fuerte, was higher on substrates with coconut fiber 40% + oil palm leaf fiber 40% + organic compost 20%, and coconut fiber 70% + organic compost 30%, while yield of the same two substrates was 15.57 and 15.44 kg/m2, respectively. Both treatments were statistically equal to the commercial coco coir substrate slabs with a yield of 14.77 kg/m2. Result attributed to the nutritional contribution of the organic compost (high K, Ca, and Mg) along with and to the effects of aeration and water retention of fibers.